Pengembangan Sistem Informasi Pemungutan Pajak Reklame Berbasis Website Menggunakan Metode Scrum Pada Badan Pendapatan Daerah Kabupaten Lombok Barat - Muhammad Imam Arsyawalfa; Eva Handriyantini (J-INTECH ( Journal of Information and Technology), 2020)
The Regional Revenue Agency of West Lombok Regency must carry out an innovation in optimizing the advertisement tax collection to balance the rapid growth of advertising and to meet the demands of the community for the availability of more effective and efficient tax service facilities. One of the innovations that must be taken is to transform manual administration into the application of information systems. The purpose of this research is to develop a Website-based Information System with the Scrum method which can facilitate the Regional Income Agency and Taxpayers in the process of collecting advertisement taxes in West Lombok Regency. The website-based information system was developed to make it easier for users because in the process of managing data and information it is faster, can be accessed at any time and wherever the user is and the available features can only be accessed by predetermined users and admins. In developing the system, the Scrum Method is used, which prioritizes the needs of the Regional Income Agency as a user who is actively involved in each stage of development. The feature development stage is divided into several product backlogs which are realized through the sprint backlog process with intensive meetings with users. The Scrum method is very supportive of the success of this research because it can be carried out in a short time, low cost and the system can be changed at any time according to user needs. From a series of research activities it is concluded that the Development of a website-based Information System with the Scrum Method which consists of service features, data collection features, determination features and billing features can help Regional Revenue Bodies and Taxpayers in the process of collecting Advertising Tax in West Lombok Regency.